Communication Analysis Of Tamang Mandailing Island Tourism Development (International Journal of Cultural and Social Science, 2022)
The title of this research is "Communication Analysis of Tamang Mandailing Natal Island Tourism Development". The purpose of this study was to find out how the communication of Tamang Island tourism development and how the supporting and inhibiting factors for the development of Tamang Mandailing Natal Island tourism were. The theory used is the Theory of Diffusion of Innovation in Development Communication as the main theory and the theory of Modernization of Development as a supporting theory. The object under study is Tamang Island tourism. This research approach is qualitative method where this qualitative research method is descriptive and tends to use analysis. The result of this research is that development communication on Tamang Island is still not optimal and is still in the failed category.